Sustainability Assessment and Reporting - Gokten, Soner; Okan Gokten, Pinar (IntechOpen, 2018)
We are more aware of the need to achieve sustainable development than ever before. One of the main factors to achieve the goal of sustainable development is sustainability assessment and reporting because it is not possible to take precautions without understanding the current situation. And also, undoubtedly, future generations have a right to know what kind of world we will leave them. This book brings together different perspectives on sustainability assessment and reporting. When you look at the chapters, you will understand that sustainability assessment and reporting are addressing interdisciplinary and vast areas. It should be because sustainability assessment and reporting cover all aspects of social, economic and environmental factors. In this five-chapter book, you will see how sustainability assessment and reporting are addressed in different areas.